The Effect of Different Soil Tillage Techniques on Weed Density, Yield And Some Yield Components of Lentil (Lens culinaris Medik.) - Hasan Kılıç; Zübeyir Türk (Trakya University Journal of Natural Sciences, 2016)
The study in which different soil tillage methods (conventional, reduced and zero tillage) and control methods of narrow leaved weeds were compared was carried out in dry farming conditions in Diyarbakır during growing season of the years 2004-2005. The weeds density, yield and yield components of lentil (Lens culinaris Medik.) were investigated. A significant difference was found between the herbicide applied (HER-1) and herbicide free groups (HER-2) (p<0.05) in terms of biological yield, harvest index, number of pods and seed per plant but there was no significant difference between the two groups in the plant height, thousand kernel weight and branch number per plant. The results showed that weed is the most important yield constraining factor in lentils and that grain yield decreased by about 25% in applications which do not include narrow leaved weed control. Although the 12 different tillage techniques applied significantly influenced the density of weed per unit, stubble coating (residue cover) rate and lentil output (emergence), they had no significant effect on other features. The highest crop yield (200.9kg/da) was obtained with the plough in summer + rototiller after rainfall + late planting (YP+YSR+TE) conventional tillage system and the lowest crop yield (108.9kg/da) was obtained with the herbicide-free, no-till and seeding by direct drill (IDTE) method.